Pengaruh Pemberian Pupuk N dan Bokashi terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays Saccharata Sturt L.) - Noor Hikmah Auliani; Bambang Fredrickus Langai; Chatimatun Nisa (Universitas Lambung Mangkurat, 2021)
This research was conducted in August - November 2019 in Tungkaran Village (Maju Bersama Farmer Group) Martapura Kab. Banjar, South Kalimantan Province and Laboratory of Agroecotechnology Production, Faculty of Agriculture, ULM Banjarbaru. This experiment used a completely randomized design (CRD) 2 factors which included 5 doses of N fertilizer (first factor) and 4 doses of bokashi fertilizer (second factor) with 2 replications. The results of this research stated that the most significant impact on the interaction of N and bokashi fertilizers were plant height (28 dast and 35 dst), plant wet weight, plant dry weight, number of seeds / rows, many cob weighted and many ears without weight. sweet corn plants, namely the N fertilizer at a dose of 90 kg N/ha to 180 kg N/ha as well as the bokashi fertilizer at a rate of 15 tons/ha.